Impact of antipsychotic treatment on methylation status of Interleukin-6 [IL-6] gene in Schizophrenia. (September 2018) - Venugopal, Deepthi; Shivakumar, Venkataram; Subbanna, Manjula; Kalmady, Sunil V.; Amaresha, Anekal C.; Agarwal, Sri Mahavir; Narayanaswamy, Janardhanan C.; Banerjee, Moinak; Debnath, Monojit; Venkatasubramanian, Ganesan
Abstract: Immunopathogenesis of schizophrenia has emerged as one of the predominant research paradigms in recent times. Based on the altered serum levels as well as gene expression, IL-6 has been considered as a peripheral biomarker of schizophrenia. However, the precise mechanism underlying the altered expression of IL6 in schizophrenia is inadequately known. Given the profound influence of environmental factors on schizophrenia risk, it is important to understand the effect of epigenetic changes on schizophrenia risk. Further, it is not known whether epigenetic changes modulate the expression of IL6 and its subsequent effects on the risk and progression of schizophrenia. In this study, we analysed and compared the methylation status of IL6 promoter sequence from −1200bp to +27bp in antipsychotic-naïve/free schizophrenia patients (N = 47) and matched healthy controls (N = 47) using bisulfite sequencing method. In addition, we also examined the methylation status in these patients at least after 3-months of treatment with antipsychotics (N = 40). At baseline, a state of hypomethylation was observed in the IL6 promoter of schizophrenia subjects in comparison to healthy controls. This state of hypomethylation was shown to be reversed by the administration of antipsychotics. In summary, our observations emphasize a significant role for IL-6 promoter methylation in schizophrenia pathogenesis as well as treatment with antipsychotic medications.